CHARACTERIZATION OF TOXOPLASMOSIS REPORTING AND SURVEILLANCE IN THE UNITED STATES - McCall, Jayden (My University, 2023)
This online experience was completed with Dr. Anne Straily from the Parasitic Diseases Branch of the Centers for Disease Control and Prevention (CDC) during the Summer of 2021. As part of this field experience, the author assisted Dr. Straily with a study investigating the surveillance systems for toxoplasmosis in states where this disease is currently categorized as “reportable.” Toxoplasmosis is a disease caused by the protozoan species Toxoplasma gondii and generally only causes clinical disease in immunocompromised individuals and children of mothers infected during gestation. This study sought to determine if toxoplasmosis would be a good candidate to become a nationally notifiable disease with the CDC. This allowed the author to use skills from several classes from the MPH coursework as well as expand on crucial writing and communication skills when preparing the results for publication and presentation to relevant individuals both within and outside the host agency. During this time, the author was also able to be a part of several other functions of this branch of the CDC, including monthly meetings and other events to learn more about their various projects and global reach. In addition to the author’s responsibilities with the CDC, he separately engaged in various teaching opportunities with his faculty mentor, Dr. Justin Kastner. This included a lecture to undergraduate students about the risks of toxoplasmosis and a lecture to graduate students about the trade-policy implications of African Swine Fever Virus over the past century (a topic that combined aspects of the author’s public health, veterinary, and PhD research-related knowledge). This experience, while primarily completed virtually due to the COVID-19 pandemic, was a rewarding opportunity for the author to learn more about how a federal public health agency like the CDC operates, to apply techniques learned from the MPH coursework regarding surveillance systems, and to gain experience in teaching future public health professionals and veterinarians
Keywords: Toxoplasmosis; surveillance systems; parasitic diseases; reportable diseases; public health; Centers for Disease Control and Prevention